Media picture of Kazakhstan: historical experience and ways of formation - Ashirbekova Г.Ш.; Abylkhanova Ә.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article analyzes the scientific concepts associated with the media images of the state, clarifies the meaning of the concepts "image of the state", "media image". Media image is a political, economic, social and psychological indicator of the state. That is why it is very important to create a media image of the state in the modern period of information warfare, geopolitical and regional conflicts. The article analyzes examples and materials from a number of foreign news agencies during the January incident. When analyzing the content, the most frequently used words related to the state, the president and the most important events are considered. Particular attention is paid to the influence of words often used in informational texts on the state media, its consequences, and a clear proposal is made on how to further form a positive image of the state through the media. The article analyzes oratory, reflections on the country in the poetry of zhyrau as an example of a media image. The reality of the Khan era is clearly visible in the poetry of zhyrau. The main requirement for creating a media image is the creation of a positive image of the state. The author analyzed more than 100 information materials in the global information space, focusing on effective methods for creating media images. The author, referring to various methods of content analysis, presents his views on public opinion.